Analisis Perencanaan Kebutuhan Sparepart dalam Mendukung Sistem Managemen Operasi Mesin Produksi: Systematic Literature Review - Sefthian Sefthian; Masduki Asbari; Nia Mintari (Yayasan Aya Sophia Indonesia, 2024)
- In Supply Chain Management, spare parts are needed to support the smooth running of production, because the spare parts used will soon be thirsty during the production process, spare parts needs are usually calculated every month depending on the production capacity, of course from various types of spare parts there are local spare parts and spare parts that must be purchased imported. The process of purchasing or procuring spare parts must go through a procurement process (Procurement) The company must ensure that the selected supplier can provide guaranteed quality materials at competitive prices Supply Chain Management for spare parts needs to include Planning, Procurement, Product Distribution and Return Management Spare parts needs also carefully affect each of the needs that have a significant impact and play a role in the smooth production process, Because they have an impact and relationship with the success of production results and the smoothness of the production process, the purpose of this research is to find out the work of the journal related to the planning of the supply of spare parts, as the first step the author starts looking for sources of academic articles both national and international, the author puts forward 6 scientific articles on the analysis of spare parts requirements for the production machine operating system, planning the right spare parts requirements is useful for the success of production.